Nobiletin, a polymethoxyflavone in citrus fruits, reduces TAFI expression in HepG2 cells through transcriptional inhibition - Takada, Kimihiko; Seike, Toru; Sasaki, Tomoyuki; Masuda, Yutaka; Ito, Akira; Ishii, Hidemi (Thrombosis and Haemostasis, 2013)
Thrombin-activatable fibrinolysis inhibitor (TAFI, carboxypeptidase B2) is a 58-kDa plasma glycoprotein secreted by hepatocytes as an inactive form. TAFI is activated by the thrombin-thrombomodulin complex, and activated TAFI (TAFIa) plays an important role in regulating the balance between coagulation and fibrinolysis through inhibition of fibrinolysis. It has been suggested that high levels of TAFI in circulating plasma increase the risks of cardiovascular death and acute phase in ischaemic stroke. However, the mechanisms of regulating TAFI expression have been unclear. The present study investigated the effects of nobiletin (a polymethoxy flavonoid contained in the rind of citrus fruits) on TAFI gene (CPB2) and TAFI antigen expression in cultured human hepatoma HepG2 cells. Nobiletin decreased the release of TAFI antigen from HepG2 cells into conditioned medium in parallel with decreased levels of CPB2 mRNA and antigen. The half-life time of CPB2 mRNA in nobiletin-treated cells was unchanged compared to that of untreated control cells. Using nobiletin-treated cells that were transfected with a luciferase CPB2 promoter reporter plasmid, activity decreased to half of that in untreated control cells. A series of luciferase reporter constructs containing 5´-flanking region deletions of the human CPB2 gene showed that the sequences from –150 bp to –50 bp were essential for transcription of CPB2 and contained an AP-1 binding sequence at ∼ –119 bp to – 99 bp in the CPB2 promoter. The amount of complexed nuclear protein and sequences from ∼ –119 bp to –99 bp was decreased in nobiletin-treated cells. ChIP assays showed that c-Jun bound to the ∼ –119 bp to –99 bp region of the CPB2 promoter and that the amount of the immunocomplex decreased after nobiletin treatment. Therefore, nobiletin-induced repression of CPB2 transcription might involve AP-1 inhibition and/or prevention of AP-1 binding in a specific region on the CPB2 gene in HepG2 cells.
Keywords: Thrombin-activatable fibrinolysis inhibitor (TAFI); fibrinolysis; AP-1; CPB2; HepG2 cells; nobiletin